Mathematical modelling of alternating electromagnetic and hydrodynamic fields, induced by bar type conductors in a cylinder - Buikis, Andris; Buligins, Leonids; Kalis, Harijs (Mathematical Modelling and Analysis, 2009)
The heating of buildings by ecologically clean and compact local devices is an interesting and actual problem. One of the modern areas of applications developed during last ten years is an effective usage of electrical energy by alternating current to produce heat energy. This work presents the mathematical model of one of such devices. It is a finite cylinder with viscous incompressible liquid and with metal electrodes of the form of bars placed parallel to the cylinder axis in the liquid. These conductors are connected to the alternating current. First published online: 14 Oct 2010